2018
DOI: 10.1128/iai.00957-17
|View full text |Cite
|
Sign up to set email alerts
|

YopN Is Required for Efficient Effector Translocation and Virulence in Yersinia pseudotuberculosis

Abstract: Type III secretion systems (T3SSs) are used by various Gram-negative pathogens to subvert the host defense by a host cell contact-dependent mechanism to secrete and translocate virulence effectors. While the effectors differ between pathogens and determine the pathogenic life style, the overall mechanism of secretion and translocation is conserved. T3SSs are regulated at multiple levels, and some secreted substrates have also been shown to function in regulation. In , one of the substrates, YopN, has long been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 54 publications
3
22
0
Order By: Relevance
“…We have recently shown that the central region encompassing aa 76-181 is dispensable for the regulatory function of YopN but required for efficient translocation of effectors YopE and YopH in Yersinia. In accordance with this, a strain expressing YopN Δ76-181 -HA failed to block phagocytosis efficiently and was more readily internalized by macrophages [31]. In this study, we identified a putative coiled-coil domain encompassing aa 80-86 within the central region.…”
Section: Introductionsupporting
confidence: 69%
See 4 more Smart Citations
“…We have recently shown that the central region encompassing aa 76-181 is dispensable for the regulatory function of YopN but required for efficient translocation of effectors YopE and YopH in Yersinia. In accordance with this, a strain expressing YopN Δ76-181 -HA failed to block phagocytosis efficiently and was more readily internalized by macrophages [31]. In this study, we identified a putative coiled-coil domain encompassing aa 80-86 within the central region.…”
Section: Introductionsupporting
confidence: 69%
“…In a recent study we showed that the central region, encompassing aa residues 76-181 of YopN, with no previously assigned function, was dispensable for the regulatory function of YopN but translocated significantly lower amounts of YopH and YopE into HeLa cells compared to the wt strain. The significance of this finding was also corroborated by the finding that deletion of this region led to impaired blocking of phagocytosis by J774 macrophages [31]. The experiments in the previous study were done by expressing YopN Δ76-181 -HA from an arabinose inducible promoter in trans in a ΔyopN mutant background.…”
Section: Construction and Characterization Of Yopn Mutants Expressed mentioning
confidence: 57%
See 3 more Smart Citations